Ensino de astronomia nos anos iniciais do ensino fundamental : como evoluem os conhecimentos dos professores a partir do estudo das ideias dos alunos em um curso de extensão baseado no modelo de investigação na escola - Bartelmebs, Roberta Chiesa (2016)
According to researches of Astronomy area of teaching, often the concepts that teachers teach in the early years of their Science class in which they work, they come from their own scholastic formation. This way the main goal of this research was to understand the evolution of the early year’s teachers' ideas about knowledge of Astronomy area, Science Nature, learning and teaching. For that, initially, we have developed a pilot course in extension mode in the extreme south of the Rio Grande do Sul State, which was attended by 10 teachers of Basic Education, totaling 20h course. After analyzing the data obtained in this pilot course, we prepared the course extension and realized new offering of the course, but only for teachers in the early years of elementary school. Thus they participated in the extension course 6 teachers working in public schools in the western region of Parana State, totaling 40 hours of course. The extension course had as a reference the proposed didactic models for curriculum design Research and School Renewal (RSR) and also the dialectic-didactic method, from which it was constructed a course based on the constructivist perspective and guided the following Problems Practical Professionals (PPP): "What are the students 'ideas on topics of Astronomy?", "How to investigate the students' ideas about topics of astronomy?" "What activities can help students' ideas on topics of Astronomy?" And "How to design and develop a teaching unit of Astronomy to the early years of elementary school?”. The methodology used for data analysis was Textual Analysis Discourse (TAD), built from the transcript of the teacher diary and researcher of the meetings recorded in audio and also the material produced by teachers over the Extension Course meetings. From the TAD emerged last five categories: 1. ideas of students about astronomy: knowing your questions and insights about what they learn at school; 2. Views of teachers about Astronomy: knowing your questions and your thoughts on what they teach; 3. learning levels built on a concept from research on astronomy activities; 4. Pedagogical applications of the use of the students 'ideas in the classroom: a reflection on the own practice and 5. Evolution of teachers’ ideas about the students’ ideas. At the end of the analysis we identified that the development of teachers occurred especially in their conception of the astronomy and on the ideas of the students. According to the transition hypothesis developed for this research, teachers evolved from an initial level, where there is recognition of the students' ideas, but there is no use of these ideas in the classroom, to an intermediate level, where teachers know the ideas of their students and include those ideas in their classes, but still no systematic way. Similarly, we conclude that when teachers are learning a new concept, as in the case of astronomy topics, and identify their own ideas on them, they become more sensitive to understand the ideas of their students. In addition, a continuing education course in the curriculum principles guided RSR enables teachers to reflect about their own practice in the classroom. We understand that this is the way so that we can conquer the long awaited change in education, in order to make the school a place where children can, in fact, build new knowledge about the world, and in the case of Astronomy, about the Universe.